Aid for Blocked Car and Towed Car Using Interent of Things Techniques - BM, Anusha; SB, Anusha; D, Deekshitha; D, Deepa; YK, Hemanth (International Journal of Computer Sciences and Engineering, 2025)
Internet of Things (IoT) plays an effective role in connecting the surrounding environmental things to the network and made easy access things from any remote location. Driving the vehicle which is blocked in the random parking areas is very difficult and time taking. The vehicle can be towed from anyone that is unknown to the driver until him/her return to the parking area. Structured modular concept is used to design the system. The system implemented using ultrasonic sensors, renesas microcontroller, GSM module, IR sensor and MATLAB. The proposed system gives the solution to drive out the blocked car and also recognized that car is towed